Do workforce diversity, inclusion practices, & organizational characteristics contribute to organizational innovation? Evidence from the U.A.E - Iffat Sabir Chaudhry (Taylor & Francis Group, 2021)
The current study attempted to determine if workforce diversity (inherent or acquired) and its inclusion practices (implementing fairness, belongingness, uniqueness, and diverse workplace climate) contribute to the innovativeness of the organizational climate. It also considered whether organizational characteristics (i.e., type, size, and industry) encourage or moderate innovation in work settings. The self-administered survey was adopted to collect responses from the employees working in different types and sizes of the organizations across the industries in the United Arab Emirates. The responses from five hundred and eleven (511) participants were analyzed using partial least square structural equation modeling (PLS-SEM). The formative and reflective measurement models and structural paths were estimated for quality checks and hypotheses testing, respectively, using Smart PLS-3. The findings confirmed that diversity and inclusion practices in the workplace significantly contribute to its innovative climate. The f 2 effect size demonstrated a stronger impact of organizational inclusion practices compared to its diversity in engaging innovation and change at the workplace. Moreover, large size organizations were more engaged in innovative activities compared to small size firms. The findings have implications for policy setters in the governmental bodies and practitioners across industries in multicultural regions, promoting culture of innovation.